How to train your dragon [videorecording (Blu-Ray)] - Deblois, Dean; Thames, Mason, 2007-; Parker, Nico, 2004-; Howell, Gabriel (Actor); Dennison, Julian, 2002-; James, Bronwyn, 1994-; Trevaldwyn, Harry; Serafinowicz, Peter, 1972-; Codd, Ruth; Wirthner, Naomi; Frost, Nick, 1972-; Butler, Gerard, 1969-; et al. (Universal, 2025)
As an ancient threat endangers both Vikings and dragons alike on the isle of Berk, the friendship between Hiccup, an inventive Viking, and Toothless, a Night Fury dragon, becomes the key to both species forging a new future together.